2012
DOI: 10.1093/cvr/cvs206
|View full text |Cite
|
Sign up to set email alerts
|

Disease characterization using LQTS-specific induced pluripotent stem cells

Abstract: This study demonstrated that iPSCs could be useful to characterize LQTS disease as well as drug responses in the LQTS patient with a novel mutation. Such analyses may in turn lead to future progress in personalized medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 34 publications
3
111
0
Order By: Relevance
“…In addition, Shiba et al [20] demonstrated that transplanted human ESC-derived cardiomyocytes electrically coupled to the host cardiomyocytes and suppressed arrhythmias in a guinea pig myocardial infarction model. Furthermore, with respect to cell transplantation in large animals, Kawamura et al [19] recently reported that cardiac cell sheets comprising purified human iPSC-derived cardiomyocytes generated using our method [18] improved cardiac function in a pig myocardial infarction model. Thus, efficacies have been achieved in cell transplantation therapies using human iPSC-derived cardiomyocytes, although many such studies showed only short-term effectiveness.…”
Section: Transplantation Of Human Psc-derived Cardiomyocytesmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, Shiba et al [20] demonstrated that transplanted human ESC-derived cardiomyocytes electrically coupled to the host cardiomyocytes and suppressed arrhythmias in a guinea pig myocardial infarction model. Furthermore, with respect to cell transplantation in large animals, Kawamura et al [19] recently reported that cardiac cell sheets comprising purified human iPSC-derived cardiomyocytes generated using our method [18] improved cardiac function in a pig myocardial infarction model. Thus, efficacies have been achieved in cell transplantation therapies using human iPSC-derived cardiomyocytes, although many such studies showed only short-term effectiveness.…”
Section: Transplantation Of Human Psc-derived Cardiomyocytesmentioning
confidence: 84%
“…The discovery and refinement of human iPSCs generation is expected to advance not only regenerative medicine but also drug discovery and analyses of genetic disorders using patient-specific iPSCs [19]. The major and common problem remaining in this quest is securing sufficient numbers of mature and functional cardiomyocytes with high purity.…”
Section: Future Directionsmentioning
confidence: 99%
“…the slow I Ks , and the rapid I Kr components of the delayed rectifier potassium currents, the sodium current I Na , and the L‐type calcium current I CaL ) varying widely even among wild‐type control hiPSC‐CMs 55, 56. Most notably, very different levels of I Ks have been described (ranging from ~ 0.3 to ~ 2.5 pA/pF 5, 57), variable observation leading to controversial conclusions: on the one hand, I Ks recapitulates physiological behaviour in playing a major role when repolarisation reserve is attenuated 58, 59; on the other, it seems to contribute to repolarisation in hiPSC‐CMs even in the absence of sympathetic stimulation 5, 36, 60, 61. The immature phenotype of all stem cell derivatives including hiPSC‐CMs is probably the reason for this variability but, independent of the cause, it is a limitation to extrapolating results obtained using hiPSC‐CMs to native – healthy and diseased – adult human CMs as discussed below.…”
Section: Pathological Phenotypes and New Mechanistic Insightsmentioning
confidence: 99%
“…A β-adrenergic agonist isoproterenol altered the activation and deactivation kinetics of the IKs and this effect was rescued by the β-blockade [6]. Egashira and co-workers also produced a disease model for LQTS type 1 [70]. In their study, the iPS cells were derived from a sporadic patient who did not have a family history of significant QT interval abnormality.…”
Section: Long Qt-syndromementioning
confidence: 99%